Validity of E-Booklet Media and Its Effect On Increasing Obesity Prevention Knowledge in Adulthood - Siti Zulekah; Mutalazimah Mutalazimah; Hermawati Soetomo; Muwakhidah Muwakhidah (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Background: Prevention efforts are needed to improve quality of life and reduce mortality due to the risk of degenerative diseases due to obesity. The aim of the study was to develop e-booklet media as an educational media for obesity prevention and analyse the effect of applying e-booklet media on increasing obesity prevention knowledge. Methods: This Research & Development research involved several subject groups including: material experts, media experts, media targets, small-scale media trial subjects and large-scale media implementation subjects. Data collection was carried out online via google form. Content validity analysis uses Content Validity Ratio (CVR) and Content Validity Index (CVI) while media validity and media objectives are based on the results of value conversion. Media trials were conducted with a knowledge pretest and post-test using a questionnaire. Analysis of the effect of media usage using the Wilcoxon test. Results: The media content validity test obtained a mean CVR value of 11.99 and CVI 0.85. Media expert validity obtained a mean value of 4.29 and media target validity obtained a mean value of 4.50. The small-scale media trial obtained an increase in knowledge of 29.64%, while the large-scale media application was 19.98%. Pretest and post-test analysis showed p=0.000. Conclusions: E-booklet media is very suitable as an educational medium to prevent adult obesity. The application of e-booklet media significantly affects the increase in knowledge about the prevention of adult obesity both on a small and large scale.